ALLELOPATHIC POTENTIAL OF AQUEOUS EXTRACT OF LEAF AND ROOT SESAME ON SICKLEPOD AND BRACHIARIA SEEDS - da Silva, Gustavo Ferreira [UNESP]; Mapeli, Nilbe Carla; Cremon, Cassiano; Chamma, Larissa [UNESP]; Luperini, Bruno Cesar Ottoboni [UNESP]; da Silva, Gabrieli Ferreira; Putti, Fernando Ferrari [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2021)
Sicklepod is an important weed in Brazil pastures, but control measures are not yet effective. Thus, allelopathy can be an alternative, due to its ecological importance and for being able to provide new structures sources for agrochemicals production. This research aimed to verify the allelopathic potential of sesame (Sesamum indicum L.) on germination and seedling development of sicklepod (Senna occidentalis L.) and brachiaria (Urochloa brizantha). The treatments were root and leaf extract of sesame, and control (distilled water). Germination percentage, speed of germination, hypocotyl and radicle length were evaluated. Speed of germination, germination percentage and radicle length had no interference from the aqueous extracts. However, in brachiaria these traits had lower values than sicklepod. Although no statistical difference was found for hypocotyl length, the leaf extract showed lower growth of this feature. Allelopathy did not affect germination and speed of germination in both species, but interfered in brachiaria seedling development.
POTENCIAL ALELOPÁTICO DEL EXTRACTO ACUOSO DE HOJA Y RAÍZ DE SÉSAMO EN SEMILLAS DE FEDEGOSO Y BRACHIARIA
POTENCIAL ALELOPÁTICO DE EXTRATO AQUOSO DE FOLHA E RAIZ DE GERGELIM EM SEMENTES DE FEDEGOSO E BRAQUIÁRIA
Keywords: Alternative control; Senna occidentalis L; Sesamum indicum L; Urochloa brizantha; Weed